Proceso del lanzamiento y masificación del medio deportivo digital Puro Vóley - Burga Errea, Ricardo Nestor (2022)
This report’s purpose is to narrate the launch of the digital sport media specialized in volleyball, named Puro Voley and its post-performance in different platforms. This was made up of an initial market identification, a targeted public group, and the development of an informative proposal. Both tasks defined the nature of the informative content that is used in the digital platform. During the last years, in our country, there have been changes that have caused modifications in the way of seeing news and getting information on different subjects, including sports. One of those changes is the overcrowding of the internet. As well, our media faced the Covid-19 pandemic since 2020. In the begging, the media had obstacles. However, the channel was able to adapt changes using new strategies, and for more than a year we could see constant growth in our medio. In this report we took into a consideration opinion of various experts and statistical data regarding the use of the internet and its consumption in order to give this report a broader vision.